Marketing dashboards, resource allocation and performance. (27th August 2020) - Clark, Bruce
Abstract : Purpose: This study aims to examine the effects of marketing dashboards on resource allocation between exploratory and exploitative activities. It proposes that tactical dashboards will lead managers to place less emphasis on exploratory activities and more emphasis on exploitative activities – with performance consequences – but that these effects will be contingent on the information and decision-making environment. Design/methodology/approach: Study hypotheses were tested using an experiment tracking objective decisions over five periods in the Markstrat simulation. A total of 105 firms, each managed by a team of Master of Business Administration students, were divided into 2 dashboard conditions and a control condition. Findings: Teams given a tactical dashboard were less likely to engage in exploratory activities when information load was high. Tactical dashboards also suppressed exploration early in the simulation. Dashboards were associated with negative firm performance overall. Research implications/limitations: The research suggests that dashboards can bias resource allocation, but the effects are contingent on the information and decision-making environment. Dashboards demonstrated a negative relationship with performance. The research lacked cognitive process measures and was limited to a single simulated industry type. Practical implications: Dashboards are not a panacea for decision-making and performance and will need to change under changing conditions. Executives should build flexibility into the design and use of their dashboards and periodically audit the value the dashboard produces. Originality/value: While widespread in marketing practice, dashboards have received little study and none involving decision-making over time and changing conditions. This research advances on limited existing work by examining objective causal effects.